Articulation points in complex networks - Liang Tian (Nature Portfolio, 2017)
An articulation point in a network is a node whose removal disconnects the network. Here the authors develop analytical tools to study key issues pertinent to articulation points, such as the expected number of them and the network vulnerability against their removal, in arbitrary complex networks.